Disease-gene discovery by integration of 3D gene expression and transcription factor binding affinities - Piro, Rosario M.; Eils, Roland; König, Rainer (Bioinformatics, 2012)
Abstract. Motivation: The computational evaluation of candidate genes for hereditary disorders is a non-trivial task. Several excellent methods for disease-gen
24 December 2012
Gesehen am 23.10.2018